Examining the causal relationships between interpersonal motivation, engagement, and academic performance among university students - Takamichi Ito; Takatoyo Umemoto (PLoS ONE, 2022)
This study investigates the validity of path models in which interpersonal motivation positively predicts behavioral, emotional, and cognitive engagement, and behavioral engagement positively predicts superior performance in collaborative learning in university classes. The path model was tested using structural equation modeling. The results of the analyses showed that weak positive paths from identified regulation to all three aspects of engagement were substantial. In addition, a weak positive path from intrinsic motivation was significant for emotional engagement. For performance, the weak positive path from behavioral engagement was statistically significant. Based on these results, the implications of the motivation theory and practice in higher education are discussed.